Obreimoff revisited: Controlled heterogeneous fracture through the splitting of mica. (September 2019) - Johnson, M.T.; Brodnik, N.R.; Ekeh, T.; Bhattacharya, K.; Faber, K.T.
Highlights: When split with a smooth wedge, muscovite mica exhibits uniform fracture along a single cleavage plane. Thickness of cleaved mica sheets determines required splitting force. Sharp thickness contrasts (heterogeneities) result in higher splitting force than in homogeneous case. Thickness contrast is analogous to compliance contrast, which may be useful in strongly-bonded layered ceramics. Abstract: Obreimoff reported his first instrumented measurements of the cleavage of muscovite mica in 1930 and that work helped to propel a greater understanding of fracture. This study builds upon that effort by investigating the role of compliance heterogeneities in brittle materials through mica splitting in a manner similar to Obreimoff. The natural layered structure of mica makes it ideal as a model system for studying fracture as crack propagation can be constrained along a single controlled cleavage plane. Cleavage through the insertion of a rounded wedge provides a straightforward mechanical setup that produces stable crack propagation, so long as the effects of friction and wedge geometry are properly considered. First, homogeneous mica sheets of uniform thickness are cleaved in ambient atmosphere to establish a baseline splitting force and critical strain energy release rate, similar Obreimoff's original work. After establishing this baseline, mica sheets with prescribed thickness heterogeneities are investigated. It is found that the splitting force required to propagate a crack along a specimen with a sharp increase in layer thickness is significantly larger than the analogous homogeneous splitting forces, even though the crack is not deflected. This indicates that a sharp increase in stiffness can produce an increase in toughness in layered structures without the need for any actual toughness contrast between constituent components or any crack deflection. This toughening effect produced by compliance contrast may have implications in the context of layered ceramic composite design, where systems are often composed of a stiff outer shell and a more compliant and damage-tolerant functional layer.